Challenges and updates in the management of eosinophilic esophagitis - Tsvetelina Velikova (Gastroenterology Review)
Eosinophilic esophagitis (EE) is a chronic T helper cell-2 mediated inflammatory condition and is considered as a primary cause of dysphagia and foregut symptoms. There are many challenges regarding the treatment options of EE. Different therapeutic approaches are best at meeting different endpoints. There are unresolved questions such as whether the goal for treatment should be to control esophageal eosinophilia and inflammation or to achieve symptomatic improvement. Still, proton pump inhibitors are used in differential diagnosis, along with their anti-inflammatory and anti-acid properties. Conducted trials continue to recommend the use of topical corticosteroids and empiric food elimination diets as first-line therapeutic modalities. The growing knowledge on the pathogenesis of EE has allowed further progression of encouraging targeted biologic therapies. However, the guidelines for EE management should be updated accordingly in the coming years, including fast evolving data on non-invasive diagnostic strategies, new treatment modalities, and the long-term prognosis of the disease.